Situación y perspectivas de la agricultura y de la vida rural en las Américas - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA)., 2019)
This report is based on the recognition that food, agricultural activity, natural resources, the environment and rural life are fundamental threads in the fabric of the well-being and development of nations. They are an essential part of daily life that provide family nutrition, ensure health, promote progress and enable the conversion of opportunities into concrete development. Therefore, the scheme recognizes that in order to appreciate the real contribution of agriculture and rural life to national development, it is necessary to go beyond traditional indicators and resort to instruments that better reflect these interrelationships. Likewise, it analyzes the situation of agriculture and rural life and the main challenges to face. An appendix of indicators and statistical references is also included, with information by countries and regions, prepared by IICA.